ON GENERALIZED VARIATIONAL INEQUALITY PROBLEMS - Golshan, H. M.; Farajzadeh, A. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2011)
In this paper, we introduce and study the generalized implicit vectorvariational inequality problems with set valued mappings in topological vector spaces. We establish existence theorems for the solution set of these problems to be nonempty compact and convex. Our results extend the results by Fang and Huang [Existence results for generalized implicit vector variational inequalities with multivalued mappings, Indian J. Pure and Appl. Math. 36(2005), 629640].